ELECTRICAL NETWORK RECONFIGURATION FOR IMPROVING THE RELIABILITY OF DISTRIBUTION SYSTEM CONSISTING OF RENEWABLE ENERGY SOURCES - Thiab, Tahreer (An-Najah National University, 2024)
This thesis evaluates the impact of network reconfiguration on improving the reliability of an electrical network with high PV penetration. The reliability of the electrical network depends on the failure rates of the components installed within it. However, for loads in the network, the failure rate and outage duration can be affected by voltage conditions. In some cases, improving the voltage can reduce the failure rate of loads, but an increase in PV penetration can lead to voltage rise, which may result in a higher failure rate. This thesis discusses how variations in PV penetration impact the reliability indices of the network and explores how reconfiguration of the network can improve its reliability. The case study uses the modified IEEE 33-bus network with a PV penetration level of 70% of the installed electrical loads. Without a PV system, the network experiences voltage drops in loads far from the connection point, leading to a high failure rate due to low voltage. However, with high PV penetration, voltage rise also affects reliability. Reconfiguring the network by connecting additional buses improves voltage conditions in both scenarios, leading to enhanced reliability indices. Without PV, the network's reliability indices are as follows: Average Interruption Rate is 83.847 failures per year, and Average Outage Duration is 1.81 hours. The indices are SAIDI: 151.694, SAIFI: 83.847, EENS: 730.407, and CAIDI: 1.809 hours. With 100% PV penetration but without reconfiguration, the Average Interruption Rate is 54.81 failures per year, and the Average Outage Duration is 1.67 hours. The indices are SAIDI: 91.6206, SAIFI: 54.8103, EENS: 441.153, CAIDI: 1.672 hours. When reconfiguration is added, the network's reliability indices improve: the Average Interruption Rate is 56.7532 failures per year, and the Average Outage Duration is 1.65 hours. The indices are SAIDI: 95.6504, SAIFI: 56.7532, EENS: 460.557, and CAIDI: 1.685 hours. The results, obtained using ETAP software, show that while adding PV reduces losses, it may decrease the reliability of the network if reconfiguration is not implemented. However, with reconfiguration, network reliability is enhanced.
تحسين موثوقية الشبكات الكهربائية التي تتضمن مصادر الطاقة المتجددة من خلال اعادة تشكيلها